“Ethnographic services are offered”: a map of ethnography as a practice in the construction of knowledge and value in marketing research companies - González Vélez, César; García González, David Fernando (Instituto de Altos Estudios Sociales, 2020)
Ethnography has been the subject of multiple approaches both at the level of its theoretical understanding and its practical implementation; authors of different disciplines —since the 19th century— have tried to demarcate their limits in conceptual, methodological and political terms. An ethnographic contemporary issue has developed in the marketing field. This article presents an overview of the use of the ethnographic methods in marketing research, a context in which ethnography is offered as a service for industries. Hence, we analyzed 47 portfolios of companies that make consumer ethnographies as a strategic tool for business development. The findings presented are part of the research project: “Business ethnographies, the integration of the ethnographic method in market research”.